The electrorheological and dielectric behaviors of conducting polymer-coated poly(ethyl methacrylate) suspensions - Kim, YD; Park, DH; Nam, SW; Park, TJ (POLYMER SOC KOREA, 2002)
The electrorheological (ER) and dielectric behaviors of the polypyrrole(PPy)-coated poly(ethyl methacrylate)(PEMA) suspensions in mineral oil were investigated. PPy was coated on PEMA particles to enhance the particle polarization, which would lead to the enhanced ER response. Various PPy-coated PEMA particles were synthesized by controlling the oxidant amount during the pyrrole polymerization, and the ER responses of their suspensions were investigated. The ER response initially increases with the oxidant amount, passes through a maximum, and then decreases with the oxidant amount. The initial increase in the ER response with oxidant amounts is due to the enhanced particle polarization with the increased particle surface conductivity. The dielectric properties of the corresponding suspensions support that the ER enhancement arises from the enhanced particle polarization. The decrease in the ER response at large oxidant amounts seems to at! se from the increased conduction between the PPy-coated PEMA particles.
Keywords: PARTICLES; FLUIDS; MODEL; POLYPYRROLE; MECHANISMS